Faricimab Outcomes in Chorioretinal Disorders: Indian Real-World Analysis (FOCUS Study) - Agrawal V; Gupta A; Agrawal V; Sheth JU (Clinical Ophthalmology, 2025)
Vishal Agrawal,1 Ayushi Gupta,1 Virendra Agrawal,2 Jay Umed Sheth3 1Department of Retina, Agrawal Hospital, Jaipur, India; 2Department of Retina, Dr. Virendra Laser Phaco Surgery Centre, Jaipur, Rajasthan, India; 3Department of Retina Services, Shantilal Shanghvi Eye Institute, Mumbai, IndiaCorrespondence: Jay Umed Sheth, Department of Retina Services, Shantilal Shanghvi Eye Institute, CS No: 3/207, 4/207, RJ Gaikwad Road, Barkat Ali Dargah Road, Wadala East, Mumbai, 400037, India, Tel +91-9961167200, Email drjay009@gmail.comPurpose: To assess the real-world efficacy and safety of intravitreal faricimab in treating Diabetic Macular Edema (DME), neovascular Age-related Macular Degeneration (nAMD), and Central Macular Edema (CME) secondary to retinal vein occlusion (RVO) in an Indian population.Patients and Methods: This single‑center, retrospective observational study reviewed the records of 49 patients (49 eyes) diagnosed with DME, nAMD, or cystoid macular edema secondary to RVO, who received a total of 150 intravitreal faricimab injections and were followed for at least 24 weeks. Patients received intravitreal faricimab injections, with follow-up at four-week intervals. Outcome measures included changes in best-corrected visual acuity (BCVA) and central macular thickness (CMT), along with resolution of intraretinal (IRF) and subretinal fluid (SRF) in nAMD patients.Results: Faricimab significantly improved BCVA and reduced CMT across all groups after a mean follow-up period of 33.31 (± 7.41) weeks. DME patients’ BCVA improved from 0.71 (± 0.36) LogMAR to 0.46 (± 0.35) LogMAR (P< 0.0001), nAMD from 1.24 (± 0.73) to 0.43 (± 0.43) LogMAR (P=0.00003), and RVO from 0.78 (± 0.32) to 0.38 (± 24) LogMAR (P=0.02). CMT decreased from 454.43 (± 164.76) μm to 255.3 (± 81.17) μm (P< 0.00001) overall. Significant reductions were also observed in IRF and SRF in nAMD patients, with IRF decreasing from 48% to 16% (P=0.008) and SRF from 100% to 20% (P< 0.00001). No significant adverse events, including intraocular inflammation (IOI), were reported.Conclusion: Faricimab demonstrated significant visual and anatomical improvements across all diagnostic groups, including off‑label use in RVO‑associated CME during the study period, showing promise as an effective treatment for DME, nAMD, and RVO. These real-world outcomes align with clinical trial data (TENAYA, LUCERNE, YOSEMITE, RHINE), underscoring faricimab’s potential as an effective, dual-action therapy for chorioretinal disorders.Keywords: faricimab, real-world, age-related macular degeneration, diabetic macular edema, retinal vein occlusion